Action Mechanisms of Du-Huo-Ji-Sheng-Tang on Cartilage Degradation in a Rabbit Model of Osteoarthritis - Chen, Chao-Wei (Hindawi Publishing Corporation, 2011)
Du-Huo-Ji-Sheng-Tang (DHJST) is a traditional Chinese herbal medicine used to treat osteoarthritis. In the present study, the therapeutic effect of DHJST on cartilage degradation in a rabbit model of osteoarthritis was investigated. In the knee joints of rabbits, anterior cruciate ligament transection (ACLT) was performed to induce experimental osteoarthritis. At the end of the sixth week, 30 rabbits with ACLT were divided into six groups, control group, DHJST group and Osaminethacine (OSA) group, which were followed for another 4 weeks. The other three groups of rabbits with ACLT were untreated with DHJST or OSA, which were sacrificed after 6 weeks, and served as 6-week time point controls. Results indicated that at the end of the sixth week after surgery, there was a significantly histological degeneration in the control group compared with the normal group. In the control group, the mean score for histological degeneration were further increases at 10th week, and there was a significantly lower mean score for histological degeneration in the DHJST group compared with the control group. To research the potential mechanism, the expression level of VEGF and HIF-1α were detected. The expression of VEGF mRNA and HIF-1α mRNA are low in normal group, while the activities increase gradually in the control group. However, compared to that of the same time point model group, activity of VEGF and HIF-1α decreased significantly in DHJST group. In conclusion, DHJST exerts significant therapeutic effect on osteoarthritis rabbits, and mechanisms are associated with inhibition of VEGF and HIF-1α expression.